Sexualidade, conjugalidade e gênero nos relacionamentos dos jovens do agreste sergipano - Cruz, Ana Patrícia dos Santos (2014)
The objective of this study was to investigate sexuality, marital and gender in romantic relationships among young wild Sergipe. This work was divided in two studies, one exploratory quantitative and the other qualitative descriptive analytical character. The first study was consisted of a survey research, was part of a national project called Brazilian Youth and the instrument for a data collection was consisted of fifty-eight questions that dealt with the aspects of the biosociodemografica characterization of participants (gender, age, race, relationship status, which the series/stage school, among others), intra-family relationships and sexual initiation. The sample was composed of one hundred sixty-eight adolescents (66,1% female) aged between fourteen and twenty-four year and average 17,21 years (DP=1,84 years) public school students; the questionnaires were administered in class and answered individually after approval of the institution and consent of participants. The results showed that boys on average dated at 1,65 persons (DP=1,08), while the average number of people that the girls dated was 1,32 (DP=0,69); male teens were on average with 4,70 persons (DP=4,48) and female were an average of 2,65 persons (DP=2,66); regarding sexual initation the boys were on average 14,94 years (DP=1,78), while girls showed a higher average, in other words, 15,63 years (DP=3,24). The second study dealt with a multiple case study from data collected by the original study. One semi-structured interviews with three participants (of different generations) who had the experience of running away was used. The interviewees were divided into three age groups: 18 years, 21 and 32 years. The interview examined the emotional and sexual lives of participants, reason (s) that led to this decision and the consequences of that act in their lives. The results showed that the reason for the escape from the parental home was linked to the difficulty of relationship they had with their parents and this was demonstrated by the lack of dialogue between the parents and the interviewees; as also another reason mentioned was the desire for more freedom and experience a different way of living that they had living in the parental home. Regarding the consequences of escape the interviewees reported that the relationship with parents has improved after they fled the home with parents, also in general have improved their lives.